2024
DOI: 10.3389/fpsyg.2023.1255548
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the links between physical activity, self-identity, social anxiety, and emotional eating among overweight and obese young adults

Huilin Wang,
Xianyi He,
Yiwei Tang
et al.

Abstract: IntroductionEmotional eating not only contributes to physical obesity but also leads to the experience of guilt and shame, exacerbating emotional problems. Increasing physical activity, adopting a balanced diet, and seeking psychological support help improve emotional eating issues in overweight or obese young adults, enhancing overall mental and physical well-being.MethodsThis study investigates the correlation between physical activity, self-identity, social anxiety, and emotional eating among 373 overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In the diverse range of school-based activities, Wang et al (2024) revealed that school-based physical activity significantly influences children’s self-identity and reduces social anxiety, also artistic sports activities have uniquely beneficial, which include artistic elements like music, choreography, and costumes, they aim to boost the sport’s esthetic value and provide an audio-visual and postural expression of fitness and esthetic appreciation ( Qi, 2018 ). This blend distinguishes artistic sports from their non-artistic counterparts by fostering physical and mental growth, offering a distinctive pathway to bolster children’s psychological health ( Zhang, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the diverse range of school-based activities, Wang et al (2024) revealed that school-based physical activity significantly influences children’s self-identity and reduces social anxiety, also artistic sports activities have uniquely beneficial, which include artistic elements like music, choreography, and costumes, they aim to boost the sport’s esthetic value and provide an audio-visual and postural expression of fitness and esthetic appreciation ( Qi, 2018 ). This blend distinguishes artistic sports from their non-artistic counterparts by fostering physical and mental growth, offering a distinctive pathway to bolster children’s psychological health ( Zhang, 2009 ).…”
Section: Introductionmentioning
confidence: 99%